DO NOT FALL to the VAPE TRAP!. (2020) - Acharya, Sudeep; Ali, Syed Ibaad; Anwar, Shamsuddin; Glaser, Allison
Abstract: Introduction: Whilst the use of combustible tobacco products continues to decline in the United States, the use of e-cigarettes has seen an explosive rise in recent years. In 2019 an outbreak on EVALI was seen across the country, highlighting the fact that e-cigarettes may not be as harmless as previously perceived. Case description: A 22-year-old male came to the emergency department complaining of vomiting and shortness of breath. Patient reported using a "pod" a day of a "JUUL" e-cigarette. Patient's oxygen requirement continued to increase and was eventually shifted to the intensive care unit and mechanically ventilated. After a course of intravenous glucocorticoids, the patient was successfully weaned off the mechanical ventilation to oral glucocorticoids and discharged. Discussion: Our patient's clinical course can be described as a "classic" case of EVALI. But in contrast to previously reported cases, our patient did not use e-cigarettes known to contain vitamin E acetate or THC two common substances implicated in EVALI. Our patient exclusively used a JUUL e-cigarette at a rate much higher than the typical user. The widespread use of JUUL and e-cigarettes especially amongst the younger demographics is especially concerning. Conclusion: Research efforts must be directed towards the substances utilized in e-cigarettes, and their use should be actively discouraged.